Characterizing changes to harm reduction site operations in British Columbia following the implementation of the decriminalization of drugs: Findings from a provincial survey - Farihah Ali; Cayley Russell; Justine Law; Sameer Imtiaz; Juls Budau; Rita Shahin; Laura MacKinnon; Dylan Griffith; Sean Patenaude; Jessica Xavier; Jürgen Rehm (Harm Reduction Journal)
Abstract Background In January 2023, British Columbia (BC), Canada, piloted a three-year decriminalization policy to address the escalating overdose crisis. The policy seeks to reduce stigma and the fear of criminal prosecution, and foster a safer and more supportive environment, encouraging greater utilization of treatment and harm reduction (HR) services among people who use drugs. There are limited data on the operational characteristics of HR sites in BC, which are essential for monitoring how decriminalization may influence service operations and utilization. This study aimed to characterize HR site operations in BC and assess any operational changes following decriminalization. Methods A cross-sectional, online self-report survey was distributed to HR sites across BC between March and April 2024. The survey was completed by a site representative, and survey questions focused on client demographics and drug use patterns, service uptake and capacity, resource and staffing demands, police activity near sites, and the availability of HR services. Changes pre-and post-decriminalization were analyzed descriptively to identify trends. Results A total of 33 HR sites completed the survey. Almost a third (30%) of sites reported an increase in client’s post-decriminalization, and 18% indicated plans to expand or modify services to meet the increasing demand. However, challenges related to staffing and resources were highlighted, with 45% of sites reporting increased staffing demands post-decriminalization, and 33% noting changes to resource needs, most of which increased. Five sites reported an increase in annual operating budgets. Nearly half (43%) of sites that experienced police activity around their site reported increased police activity post-decriminalization. Moreover, approximately one-fifth (21%) of sites received formal decriminalization training. Conclusions HR sites have experienced an increase in client engagement post-decriminalization, reporting challenges related to site capacity and funding, and emphasizing the need for additional investments to support and expand HR services. Consideration should be given to needs-based planning and providing decriminalization training to HR staff. Moreover, steps are necessary to address the continued police presence near sites, which may hinder service uptake and perpetuate stigma. Addressing these gaps is critical for improving health system engagement for people who use drugs and achieving the goals of decriminalization.